International trade law, political economy and rules of origin : a plea for a reform of the WTO regime on rules of origin - Hirsch, Moshe (2002)
Exposes the basic elements of the political economy of international trade. Presents a political economy analysis of the essential functions of rules of origin (ROO) in the world trading system. Discusses the widening use of ROO as a strategic trade instrument. Employs political economy analysis to identify the principal factors that explain this accelerated trend. Suggests legal mechanisms for reforming the current WTO regime on ROO. Concludes that the combination of international trade law and political economy analysis may be a valuable tool to promote trade liberalization in the sphere of ROO, as well as in other domains that are susceptible to protectionism.